CULTIVATION OF HUMAN LIVER CELLS AND ADIPOSE-DERIVED MESENCHYMAL STROMAL CELLS IN PERFUSION BIOREACTOR - Yu. В. Basok; A. M. Grigoryev; L. A. Kirsanova; N. P. Shmerko; К. M. Khizroev; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Aim: to show the progress of the experiment of cultivation of human liver cells and adipose-derived mesenchymal stromal cells in perfusion bioreactor.Materials and methods. The cultivation of a cell-engineered construct, consisting of a biopolymer microstructured collagen-containing hydrogel, human liver cells, adipose-derived mesenchymal stromal cells, and William’s E Medium, was performed in a perfusion bioreactor.Results. On the 7th day large cells with hepatocyte morphology – of a polygonal shape and a centrally located round nucleus, – were present in the culture chambers of the bioreactor. The metabolic activity of hepatocytes in cell-engineered constructs was confi rmed by the presence of urea in the culture medium on the seventh day of cultivation in the bioreactor and by the resorption of a biopolymer microstructured collagen-containing hydrogel.